Novel UWB Microstrip Antenna Structures with Defected Ground Structure - Saida Elajoumi; A. Tajmouati; J. Zbitou; A. Errkik; L. El Abdellaoui; A.M. Sanchez (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents the design of new compact printed antennas for Ultra Wide Band applications, fed with a microstrip-line. The proposed designs consist of a patch antenna with defected ground, which are fed by 50Ω microstrip transmission line. The frequency range is 3.1-10.6 GHz which is the Federal Communication Commission (FCC) band of UWB. The proposed antennas are easy for integration with microwave circuits. They are validated into simulation by using two electromagnetic solvers CST-MW and Ansoft HFSS. The simulated input impedance bandwidth ranging 3GHz to more than 14 GHz is obtained with return loss less -10dB, and exhibits good UWB characteristics. The measured parameters are good agreement with the simulation. Therefore these antennas offer excellent performance for UWB system.